2016
DOI: 10.1093/bjsw/bcv143
|View full text |Cite
|
Sign up to set email alerts
|

‘Everyday Advocates’ for Inclusive Care? Perspectives on Enhancing the Provision of Long-Term Care Services for Older Lesbian, Gay and Bisexual Adults in Wales: Table 1

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms 'Everyday advocates' for inclusive care. 'Everyday advocates' for inclusive care. 2 AbstractThis paper centres on a neglected area of social work with older people-the social inclusion of older lesbian, gay and bisexual (LGB) adults in long-term care environments. The translation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…Our objective is to examine the significance of home and place for LGB adults (50+ years) through three lenses: rural places as “home”; connections to LGB communities across online and geographical communities; and anticipation of social care provision in the home. We present interview findings from a mixed‐methods study on the social inclusion of older LGB adults in Wales, which concluded in 2013 (see Willis, Maegusuku‐Hewett, Raithby, & Miles, ; Willis, Maegusuku‐Hewett, Raithby, & Miles, ). Findings indicate a contradictory relationship to rurality and geographical community, and ambivalence expressed at the prospect of receiving care services at home.…”
Section: Introductionmentioning
confidence: 99%
“…Our objective is to examine the significance of home and place for LGB adults (50+ years) through three lenses: rural places as “home”; connections to LGB communities across online and geographical communities; and anticipation of social care provision in the home. We present interview findings from a mixed‐methods study on the social inclusion of older LGB adults in Wales, which concluded in 2013 (see Willis, Maegusuku‐Hewett, Raithby, & Miles, ; Willis, Maegusuku‐Hewett, Raithby, & Miles, ). Findings indicate a contradictory relationship to rurality and geographical community, and ambivalence expressed at the prospect of receiving care services at home.…”
Section: Introductionmentioning
confidence: 99%
“…To some extent this is borne out by research with care staff which has identified good intentions but low levels of awareness amongst care home staff of the needs of LGBT residents (Hafford-Letchfield, Simpson, Willis, & Almack, 2018;Simpson, Almack, & Walthery, 2018;Willis, Hafford-Letchfield, Almack, & Simpson, 2017). Researchers have identified that to advance social inclusion of LGBT citizens in residential settings is complex and requires working at structural, cultural and individual levels of provision and for a more explicit implementation of equality legislation (Hafford-Letchfield et al, 2018;Willis, 2017;Willis, Raithby, Maegusuku-Hewett, & Miles, 2017). Such issues may be compounded at the end of life (Almack, 2018, Almack, Seymour, & Bellamy, 2010Bristowe et al, 2018).…”
Section: Problematising the Lgbt Acronymmentioning
confidence: 99%
“…Demonstrations of affection among residents calls for censorship from the staff and residents, especially when expressions of intimacy are legitimized as being part of a "couple". Homosexual expressions are often pathologized, sinful, and socially degraded with heteronormativity predominant, despite this also motivating innumerable repressions (10) . Upon the dilemmas encountered on a daily basis, it becomes necessary to consider a myriad of legal, ethical, and institutional requirements, in addition to the residents' needs (11) .…”
Section: Discussionmentioning
confidence: 99%